On the move to meaningful internet systems. OTM 2018 Conferences : Confederated International Conferences: CoopIS, C&TC, and ODBASE 2018, Valletta, Malta, October 22-26, 2018, Proceedings /: OTM 2018 Conferences : Confederated International Conferences: CoopIS, C&TC, and ODBASE 2018, Valletta, Malta, October 22-26, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available